Glottal stop variation in Libyan Arabic (Journal of Academic Research, 2023)
The glottal stop [ʔ], called hamza1 in Arabic, undergoes different processes in different phonological environments. Sometimes, this consonant is deleted. Since this deletion is accompanied by compensatory lengthening, the moraic structure of the syllable from which the glottal stop deletes is unaffected. Other times, the quality of the vowel preceding the dropped hamza changes. So, instead of the low vowel /aa/, we end up having the mid vowel [ee]. Intervocalic ʔ is replaced by the glide y, which may resyllabify as a coda. Finally, across a word boundary, the hamza gets deleted, causing the consonant preceding it to attach to the following vowel. This paper sheds light on these processes as attested in one variety of Arabic, namely the variety spoken by the dwellers of the city of Misrata, Libya, henceforth Misrata Libyan Arabic (MLA).